Quantitative and Qualitative Factors that Leads to Slip and Fall Incidents - Syahrom, Ardiyansyah; Ahmad, Norazrin Azwani; Tap, Masine Md.; Rohani, Jafri Mohd.; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2017)
This book investigates the factors that lead to slip and fall incidents and establishes a relationship between the coefficient of friction (COF), floor slipperiness and floor roughness. It also examines human perception of slipperiness through measured coefficient of friction (COF). On the basis of questionnaire surveys among manufacturing workers, it identifies potential risk factors and assesses human perceptions of slipperiness. It also uses a tribology approach to relate the interaction between contaminants, floor and footwear materials.
Introduction -- Factors Lead to Slip-and-Fall Incidents -- Relationship between Coefficient of Friction (COF) with Floor -- Slipperiness and Roughness -- Human Perception of Slipperiness through measured COF -- Conclusion.
Keywords: Facility management; Biomedical engineering; Coatings; Tribology; Corrosion and anti-corrosives.; Facility Management; Biomedical Engineering and Bioengineering; Coatings; Tribology; Corrosion